PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DOMESTIK DI KOTA DENPASAR - I Wayan Wirawan (STIMI Handayani Denpasar, 2020)
In the last 5 years, the landfill has not been able to accommodate the piles of garbage, even in 2007 it is estimated that the landfill is only 6 months old. To improve the effectiveness of waste management, the DTRKP (Department of Urban Spatial Planning and Settlements) promotes a reduce, reuse and recycle (3R) program by placing 13 units of containers and some containers that use organic waste into compost. Until now, the role of the community in general is limited to garbage disposal, which has not yet reached the stage of waste management that can benefit the community. Simple waste management by separating organic and inorganic waste requires intensive socialization from the government to the community. The concept of this approach puts the community as the main party or center of development that is encouraging community participation and partnership. In addition, the role of the community itself is a manifestation of efforts to increase community capacity derived from the willingness and ability of the community to be involved in each stage of development. If the domestic waste problem is not treated properly, it will clearly have an impact on environmental pollution and the reduction in aesthetic value. This occurs due to lack of sense of responsibility and the very low understanding of the community regarding the benefits of cleanliness. Community participation in managing domestic waste is highly dependent on the understanding and willingness of the community to maintain and create a clean environment. Besides that, the ability of the community to contribute to domestic waste management will also depend very much on the income of the community, especially people in Denpasar City.